ALBERT SCHWEITZER’ ETHICS: APPLIED ASPECT - Gaertner, H.; Stelcer, B.; Wissel, E. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The authors discuss the activities and achievements of Albert Schweitzer in their principal fields: music and musicology, philosophy and theology, and medicine and hospital management. They also describe Schweitzer’s successive hospitals in Lambarene (Gabon) during the years of 1913-2013.